Learning Innovations in Islamic Religious Education in the Context of Increasing the Effectiveness of Learning - Susanti, Desi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
To create effective Islamic Religious Education learning in the classroom, teachers need to innovate learning, so that learning in the classroom is not monotonous and not boring, so that learning achievement targets are not met. Innovations carried out by teachers can be carried out by using various methods, using media, evaluation and so on. Considering the importance of innovation in the Islamic Religious Education learning system, the problem formulation in this research is; 1) What are the innovations in learning Islamic Religious Education at PKBM (Learning Activity Center Of Public) Literasi Bangsa Kejayan Pujer Bondowoso? 2) What are the results of the implementation of Islamic Religious Education learning innovations at PKBM Literasi Bangsa Kejayan Pujer Bondowoso?This research uses a qualitative approach with a "naturalistic phenomenological" approach, namely understanding the meaning of events and their relationships to people in certain situations. In this case, the researcher acts as the main instrument for data collection. In selecting informants, the "purposive sampling" technique will be used. To select and determine informants, the snowball sampling technique was used. The data collection technique is carried out by; Involved observation (participant observation), in-depth interviews (in-depth interviews) and documentation. Meanwhile, data analysis was carried out from the time of data collection. Before the data is analyzed by researchers, the data is first processed, then edited, followed by (coding). Checking the validity of the data is carried out by checking the methodology used, checking the report results and triangulation. The results of research while in the field are as follows; 1) Innovation in learning Islamic Religious Education at PKBM Literasi Bangsa Kejayan Pujer Bondowoso is carried out by means of; preparing learning tools, using various methods in the classroom learning system, managing various classes, using information technology-based learning media, and conducting ongoing evaluations of learning activities in order to get feedback in determining plans for the next learning program. 2) The results of the implementation of Islamic Religious Education learning innovations at PKBM Literasi Bangsa Kejayan Pujer Bondowoso appear in; increasing student motivation to learn, increasing student interest in learning, achieving learning goals, and increasing student achievement both academic and non-academic.